Pd Clusters on Schiff Base–Imidazole-Functionalized MOFs for Highly Efficient Catalytic Suzuki Coupling Reactions - Liu, Yangqing; Sun, Jingwen; Fan, Lan; Xu, Qi (Frontiers in Chemistry, 2022)
Subnanometer noble metal clusters have attracted much attention because of abundant low-coordinated metal atoms that perform excellent catalytic activity in various catalytic processes. However, the surface free energy of metals increases significantly with decreasing size of the metal clusters, which accelerates the aggregation of small clusters. In this work, new Schiff base–imidazole-functionalized MOFs were successfully synthesized via the postsynthetic modification method. Highly dispersed Pd clusters with an average size of 1.5 nm were constructed on this functional MOFs and behaved excellent catalytic activity in the Suzuki coupling of phenyboronic acid and bromobenzene (yield of biaryl >99%) under mild reaction conditions. Moreover, the catalyst can be reused six times without loss of activity. Such catalytic behavior is found to closely related to the surface functional groups that promote the formation of small Pd0 clusters in the metallic state.